Experimental study on the rise of aqueous foams in vertical pipes - Álvarez Salazar, Valeriano S.; Sigalotti, Leonardo Di G.; Medina Ovando, Abraham; Carvajal-Mariscal, Ignacio; Klapp, Jaime (Frontiers in Physics, 2022)
In this paper we report experiments on the growth of dry foams and their rise in vertical pipes of different circular cross-sectional radii with length over diameter ratios in the interval $25≤ h/D≤ 80$ for applications in the study of fracture stimulation in enhanced oil recovery processes. Air injection at the bottom of the pipes is performed at a constant flow rate by means of a single capillary tube. The formation and rising of the foam was investigated for two different cases: (a) when the top cap of the vertical pipes is open and (b) when it is closed. We find that the position and velocity of the foam front as well as the foam dispersivity are both dependent on the pipe diameter and on whether its top end is open or capped. When the top is open, the foam column grows faster compared to the case when it is sealed. In pipes with $h/D≥ 30$, the growth rate is nonlinear and faster than in pipes with $h/D<30$ in which cases the foam rises at an almost constant rate. As the diameter of the pipe increases, the size of the produced bubbles also increases. In closed-top pipes the foams tend to be more homogeneous than in open top pipes. The experimental observations indicate that under foam drainage driven by gravity, the liquid flow velocity across the Plateau borders is indicative of a drainage model based on a plug-like flow in channels with fully mobile interfaces, where viscous dissipation occurs only in the nodes.